Frequency of Neonatal Respiratory Distress among Newborns of Mothers with Preterm Premature Rupture of Membranes in Tertiary Care Hospital: Neonatal Respiratory Distress among Newborns of Mothers with Preterm Premature Rupture of Membranes - Nazir, Maryam; Saifullah, Sadaf; Anwar, Sadia; Inayat, Kosar; Umar, Saima; Bibi, Najma (Pakistan Journal of Health Sciences, 2024)
Respiratory distress leads to neonatal morbidity and mortality. The premature rupture of membranes before labor at less than 37 weeks. Objectives: To determine the frequency of neonatal respiratory distress in newborns delivered with preterm premature rupture of membranes. Methods: Cross-sectional study conducted in the Gynecology unit at Ayub Teaching Hospital Abbottabad from 1-4-2018 to 1-9-2018. Sample size 244 was calculated using WHO software by non-probability consecutive sampling using a convenience sampling technique. Pregnant women with singleton pregnancy, gestation 34-36 weeks, parity 0-4 with preterm rupture of membranes were included. After birth, an examination of the newborn for features of respiratory distress was done by a neonatologist. Data were analyzed with SPSS version 22.0. Mean ± SD was presented for quantitative variables and frequency percentage was computed for qualitative variables like respiratory distress. Results: The mean age was 28.733 ± 2.71, the mean gestational age was 34.750 ± 0.65 and the mean parity was 1.028 ± 1.11. Respiratory distress was observed in 40.2% of newborns. Stratification of Respiratory Distress concerning maternal age, parity, and gestation done. This was 87.9 % in newborns of women aged 18-27 and 25.3% in women aged 28-35 years. 43% of newborns developed respiratory distress at gestation less than 35 weeks and 20% at gestation more than 35 weeks. Conclusions: It was concluded that the frequency of neonatal respiratory depression was 40% in newborns with premature rupture of membranes. It was more common in younger ages and at less than 35 weeks of gestation.